2013
DOI: 10.1007/s00784-013-0924-4
|View full text |Cite
|
Sign up to set email alerts
|

Light curing through glass ceramics with a second- and a third-generation LED curing unit: effect of curing mode on the degree of conversion of dual-curing resin cements

Abstract: When light curing a given cement, the higher irradiances of the third-generation LED curing unit resulted in similar DC compared to the second-generation one, though at shorter light curing times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 24 publications
9
65
0
6
Order By: Relevance
“…In the present study, the thickest tested materials were 2 mm, which was enough to reduce the DC of resin cement (13). Flury et al (23) showed that the irradiances from two curing units decreased by >80% through IPS Empress CAD and IPS e.max CAD (Ivoclar Vivadent) 1.5-mm discs. However, the DC for the RelyX Unicem 2 was not reduced, which corroborates the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the thickest tested materials were 2 mm, which was enough to reduce the DC of resin cement (13). Flury et al (23) showed that the irradiances from two curing units decreased by >80% through IPS Empress CAD and IPS e.max CAD (Ivoclar Vivadent) 1.5-mm discs. However, the DC for the RelyX Unicem 2 was not reduced, which corroborates the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Second-generation LED curing units typically reach irradiances of 1,200 to 1,500 mW/ cm 2 . The third-generation of LED curing units contains multiple diodes, and recently a third-generation LED curing unit was marketed (VALO, Ultradent), which is claimed to reach irradiances of up to 3,200 mW/cm 2 depending on the chosen mode 14) . Dental visible light curing materials generally contain a diketone-type photoinitiator that absorbs light in the 400-to 500-nm range covered by the blue light from the visible spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, na presente pesquisa, este dispositivo foi empregado com o objetivo de demonstrar o comportamento das duas resinas, considerando diferentes resinas e espessuras. Outros trabalhos também empregam radiômetros manuais com a finalidade de mensurar a perda de luz através de diferentes materiais [24][25][26] . Outro aspecto relevante refere-se à intensidade média de luz empregada durante o experimento que foi de 1000 mW/cm 2 , a qual é considerada alta.…”
Section: Discussionunclassified